Prophylactic Use of Ondansetron for Hypotension Prevention in Cases Undergoing Cesarean Section Post-Spinal Anesthesia - Kelash Kumar, Ali Aftab, Anil Kumar, Pervaiz Ali, Sandeep Kumar, Kazi Iftikhar Qureshi (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ondansetron is being administrated to prevent post spinal hypotension and its affects are promising. Globally, researches being conducted to identify the prophylactic effects of ondansetron. Aim: To determine the frequency of maternal hypotension with or without intravenous administration of ondansetron in cases undergoing cesarean section post-spinal anesthesia. Study design: Randomized controlled trial Place and duration of study: Jinnah Postgraduate Medical Centre, Karachi from 1st February 2017 to 1st August 2017. Methodology: Eighty four pregnant females between 18-35 years of age enrolled for cesarean-section under spinal anesthesia were included. Patients having a history of cardiorespiratory or renal disorders, as well as bradycardia or tachycardia, hypo/hypertension and or hyperglycemia were excluded. The patients were randomly divided into Group A (ondansetron) and Group B (control) by using codes placed in sealed, sequentially numbered envelopes. The mean value of arterial blood pressure and of the heart rate was documented at 3 min interval for 10 minutes and then every 5 minutes till 30 minutes after spinal anesthesia. Results: The mean age of patients in group A was 26.57±5.28 years and in group B was 26.88±4.62 years. Thirty two (38.10%) were ASA I and 52 (61.90%) were ASA II. The mean age of patients in group A was 39.36±1.65 weeks and in group B was 39.79±1.47 weeks. Mean arterial pressure was 138.44±13.59mmHg. Frequency of maternal hypotension in Group A was seen in 08 (19.05%) while in Group B was seen in 22 (52.38%) patients (p=0.001). Conclusion: There is less maternal hypotension with intravenous administration of ondansetron in patients undergoing cesarean section under spinal anesthesia. Keywords: Spinal anesthesia, Hypotension, Ondansetrone